2004
DOI: 10.1002/j.1939-4640.2004.tb03169.x
|View full text |Cite
|
Sign up to set email alerts
|

Restorative Increases in Serum Testosterone Levels Are Significantly Correlated to Improvements in Sexual Functioning

Abstract: It is recognized that testosterone (T) levels decrease in men with age, as does sexual function. We hypothesize that T supplementation in hypogonadal men with sexual dysfunction will restore certain elements of sexual function. Hypogonadal male subjects (total T ≤ 300 ng/dL, n = 406, mean age 58 years) reporting one or more symptoms of low testosterone were randomized to T gel (50 mg/d and 100 mg/d), T patch, or placebo. Twenty‐four‐hour pharmacokinetic profiles for T were obtained. The 3 primary end points ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 23 publications
0
46
0
3
Order By: Relevance
“…In one study, threshold serum T values (C avg ) were identified above which significant improvements were noted: 500 ng/dl for the frequency of sexual intercourse and 600 ng/dl for self-rated sexual desire (Figure 1). 10 The frequency of night time erections rose significantly even when serum T levels were low-normal (C avg ¼ 400 ng/dl), suggesting that this androgenic effect may be among the earliest to be observed during TRT.…”
Section: Clinical Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…In one study, threshold serum T values (C avg ) were identified above which significant improvements were noted: 500 ng/dl for the frequency of sexual intercourse and 600 ng/dl for self-rated sexual desire (Figure 1). 10 The frequency of night time erections rose significantly even when serum T levels were low-normal (C avg ¼ 400 ng/dl), suggesting that this androgenic effect may be among the earliest to be observed during TRT.…”
Section: Clinical Studiesmentioning
confidence: 97%
“…6 Application-site reactions represent the most frequent complaints with both T gels, occurring in up to 5% of patients. 6,7 With regard to prostate safety, 2.8-18.8% of 106 men receiving T gel (AndroGel) 50-100 mg experienced prostate enlargement or elevation in PSA 6 Additional study findings on the effects of T gels on PSA levels 10,12 are shown in Table 1.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…The value for restoring sexual functions in hypogonadal men receiving treatment with testosterone gel is well documented [5,6,[8][9][10]. A recent study shows the adjunctive role of testosterone gel with sildenafil [11].…”
Section: Testosterone Gelmentioning
confidence: 99%
“…Recently, in a large cohort of 406 men (mean age 58 years and total testosterone < or = 300 ng/dL) a clear relationship was reported between restoring serum testosterone to the normal range and improvement of certain parameters of sexual functioning, such as sexual desire, nocturnal erections and frequency of intercourse [20]. Remarkably, in this study the results of testosterone administration with a 100 mg gel were superior to those of 50 mg gel or a testosterone patch, raising the issue of threshold values of testosterone for sexual functioning in elderly men.…”
Section: Effects Of Testosterone Therapy To Elderly Men With Edmentioning
confidence: 99%